Smart cards and the fingerprint: a framework for user identification and authentication - Omar, M. H.; Din, Roshidi; Tahir, H. M. (Universiti Utara Malaysia, 2003)
Access control has been a great concern in this Information and Communication Technology (ICT) era. The need to control access to certain information and resources has been taken seriously by the ICT community. This research believes that no single security method, algorithm, key or procedure is entirely secure. Hence, a combination of multiple security components is mandatory to provide a high level of protection against fraud and other threats. This research combines two security components, which are the smart card and fingerprint recognition. It looks into the vulnerabilities of magnetic-stripe cards and Personal Identification Numbers (PIN) or passwords widely used in systems today. As a result, the research proposed a framework for user identification and authentication in automatic-teller-machine (ATM) systems using fingerprints and smart cards as opposed to the PIN and magnetic-stripe cards.